NITROGEN PRIMING SOURCES AFFECT THE SEED GERMINATION, GROWTH AND FRUIT ATTRIBUTES OF BITTER GOURD - ANWAR, M; WAHOCHO, NA; MEMON, NUN; KANDHRO, MN; ABBAS, T; TALPUR, KH; JAMALI, MF; KAKAR, K (Biological and Clinical Sciences Research Journal, 2024)
The production of bitter gourd is often hampered by low seed germination rates due to its hard seed coat, which leads to sluggish seed germination, poor stand establishment, and yield losses. Nutrient seed priming has emerged as a promising technique to overcome these challenges by enhancing seed vigor and germination performance, hence explored in bitter gourd. The study pursued a thorough assessment of the effects of seed priming with nitrogen sources (Urea and KNO3) on germination, growth, fruit characteristics, and shelf life of bitter gourd cultivars (Fighter and Palee). The treatments included unprimed seeds (Control), seed priming with tap water, seed priming with urea solution (1% and 2%), and seed priming with KNO3 solution (1% and 2%). The results revealed that priming with KNO3 at 2% concentration emerged as the superior treatment across multiple growth parameters, yielding the highest germination rate (85.40%), longest vine length (179.34 cm), and most abundant leaf count vine-1 (298.89). This priming also led to a significant reduction in days to flowering and enhanced the fruiting phase, resulting in earlier fruit development (59.53 days), increased fruit length (22.80 cm), and the highest single fruit weight (104.87 g). The priming with KNO3 at 2% also showed promising results for fruit shelf-life characteristics and improved shelf life (6.07 days) and minimal weight loss (4.61%). Between the two varieties, ’Palee’ consistently outperformed ’Fighter,’ showcasing superior performance for all the attributes observed in the study. These findings highlight the significant role of priming in enhancing the germination, fruit characteristics and shelf life of bitter gourd.